Interleukin-34 Mediates Cross-Talk Between Stromal Cells and Immune Cells in the Gut - Monteleone, Giovanni; Franzè, Eleonora; Troncone, Edoardo; Maresca, Claudia; Marafini, Irene (Frontiers in Immunology, 2022)
Initially known as a cytokine produced by and regulating the function of monocytes and macrophages, interleukin-34 (IL-34) can be synthesized by many cell types and interacts with receptors expressed by multiple immune and non-immune cells. IL-34 is constitutively expressed in the healthy human small intestine and colon and its production is markedly increased in damaged gut of patients with Crohn’s disease and patients with ulcerative colitis, the main forms of chronic inflammatory bowel diseases (IBD) in human beings. Circumstantial evidence suggests that, in these pathologies, IL-34 plays a crucial role in mediating cross-talk between immune cells and stromal cells, thereby promoting activation of signalling pathways, which amplify the ongoing mucosal inflammation as well as production of fibrogenic molecules. In this article, we summarize the available data supporting the multiple effects of IL-34 in human IBD with particular attention to the role of the cytokine in immune and stromal cell interactions.